2008
DOI: 10.4049/jimmunol.181.8.5249
|View full text |Cite
|
Sign up to set email alerts
|

Blimp-1 Induced by IL-4 Plays a Critical Role in Suppressing IL-2 Production in Activated CD4 T Cells

Abstract: Although an inhibitory function of IL-4 in CD4 T cell IL-2 production has long been recognized, a mechanism mediating the inhibition remains unclear. In this study we demonstrate that IL-4 displays a potent suppressive function in IL-2 production of activated CD4 T cells through STAT6. IL-4-induced IL-2 suppression required IL-2 because IL-2 neutralization restored the production of IL-2 even in the presence of IL-4. In vivo, enhanced IL-2 production was found in nematode-infected IL-4- or STAT6-deficient anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(65 reference statements)
0
13
0
3
Order By: Relevance
“…JunB , whose expression is selectively upregulated in Th2 cells, collaborates with c-Maf in inducing IL-4 production through binding to the Il4 promoter (170). Expression of Blimp-1, an important transcription factor for long-lived plasma cells, is induced in Th2 cells where it suppresses IFN-γ and IL-2 production (171173). Blimp-1 has recently been reported to oppose the expression of Bcl-6 and thus to inhibit Tfh differentiation (101).…”
Section: Transcription Factors For T Helper Cell Fate Determinationmentioning
confidence: 99%
“…JunB , whose expression is selectively upregulated in Th2 cells, collaborates with c-Maf in inducing IL-4 production through binding to the Il4 promoter (170). Expression of Blimp-1, an important transcription factor for long-lived plasma cells, is induced in Th2 cells where it suppresses IFN-γ and IL-2 production (171173). Blimp-1 has recently been reported to oppose the expression of Bcl-6 and thus to inhibit Tfh differentiation (101).…”
Section: Transcription Factors For T Helper Cell Fate Determinationmentioning
confidence: 99%
“…Blimp-1 attenuates IFN-γ production in CD4 + T cells activated in vitro under nonpolarizing conditions and in vivo [11, 35, 38]. Wang et al showed that Blimp-1 is very strongly induced and plays a role in IL-2 inhibition when naive T cells are stimulated in the presence of IL-4, both in vitro and in vivo [46]. IL-2 is critical for T cell immunity to promote proliferation, activation and differentiation of T cells [47]; it induces Blimp-1 expression in activated T cells and inhibits its own production through the induction of Blimp-1 in a negative feedback loop [15, 16].…”
Section: The Effects Of Blimp-1 On T Cell Functionsmentioning
confidence: 99%
“…In the absence of Blimp-1, mice develop a lethal multiorgan inflammatory disease caused by an accumulation of effector and memory T cells (116), thus making Blimp-1 an important regulator of the adaptive immune response. Blimp-1 is also required for repression of Il2 transcription in T cells, resulting in an autoregulatory loop that controls immune responses (117, 118). In addition, Blimp-1 is crucial for the IL-27-dependent induction of IL-10 by Th1 cells (so-called Tr1 cells) following infection with Toxoplasma gondii or influenza A virus (119, 120).…”
Section: Interactions and Potential Roles Of G9amentioning
confidence: 99%